Makna Kesatuan Roh berdasarkan Efesus 4:3-6 dan Implikasinya dalam Kehidupan Orang Kristen Masa Kini - Lani, Guntur Andika Alan Roh (Sekolah Tinggi Teologi Borneo, 2023)
Abstract: The different backgrounds of the congregation pose challenges in the process of faith growth. In the fellowship of fellow congregations, what is needed is unity, which unity is what binds believers in one community called the body of Christ. The unity of the Spirit is the basis for the unity of the congregation as a whole. The method used in this writing is qualitative literature with text analysis methods. From the results of this research, it was found that the unity of the Spirit is the work of the Holy Spirit for believers who have been called from darkness to the light of Christ. This unity is not based on physical and mental unity but is a moral and spiritual unity between Christ and believers which is based on the Holy Spirit. This unity also influences the attitude of life of Christians in their relationship with God and also with each other.Keywords: Unity of the Spirit, Ephesians 4:3-6, Christian LifeAbstrak: Latar belakang jemaat yang berbeda menjadi tantangan tersendiri dalam proses pertumbuhan iman. Dalam persekutuan sesama jemaat yang diperlukan adalah kesatuan, yang mana kesatuan inilah yang mengikat orang percaya dalam satu komunitas yang disebut tubuh Kristus. Kesatuan Roh menjadi dasar bagi kesatuan jemaat secara keseluruhan. Metode yang digunakan dalam penulisan ini adalah kualitatif literatur dengan metode analisa teks. Dari hasil penelitian tersebut didapati bahwa kesatuan Roh merupakan karya Roh Kudus bagi orang-orang percaya yang sudah dipanggil dari kegelapan kepada terang Kristus. Kesatuan ini tidak dilandasi dengan kesatuan jasmani dan mental melainkan merupakan kesatuan moral dan spritual antara Kristus dan orang-orang percaya yang dilandasi oleh Roh Kudus. Kesatuan ini juga memperngaruhi sikap hidup orang Kristen dalam hubungannya denga Tuhan dan juga dengan sesamanya.Kata Kunci: Kesatuan Roh, Efesus 4:3-6, Kehidupan Orang Kristen.